Molecular analysis of exons 8, 9 and 10 of the fibroblast growth factor receptor 2 (FGFR2) gene in two families with index cases of apert syndrome (2015)
Introduction: Apert syndrome (AS) is a craniosynostosis condition caused by mutations in the Fibroblast Growth Factor Receptor 2 (FGFR2) gene. Clinical features include cutaneous and osseous symmetric syndactily in hands and feet, with variable presentations in bones, brain, skin and other internal organs. Methods: Members of two families with an index case of Apert Syndrome were assessed to describe relevant clinical features and molecular analysis (sequencing and amplification) of exons 8, 9 and 10 of FGFR2 gen. Results: Family 1 consists of the mother, the index case and half -brother who has a cleft lip and palate. In this family we found a single FGFR2 mutation, S252W, in the sequence of exon 8. Although mutations were not found in the study of the patient affected with cleft lip and palate, it is known that these diseases share signaling pathways, allowing suspected alterations in shared genes. In the patient of family 2, we found a sequence variant T78.501A located near the splicing site, which could interfere in this process, and consequently with the protein function. © 2015. Universidad del Valle.